If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(x + 5) = 9(x + 5) Reorder the terms: 10(5 + x) = 9(x + 5) (5 * 10 + x * 10) = 9(x + 5) (50 + 10x) = 9(x + 5) Reorder the terms: 50 + 10x = 9(5 + x) 50 + 10x = (5 * 9 + x * 9) 50 + 10x = (45 + 9x) Solving 50 + 10x = 45 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 50 + 10x + -9x = 45 + 9x + -9x Combine like terms: 10x + -9x = 1x 50 + 1x = 45 + 9x + -9x Combine like terms: 9x + -9x = 0 50 + 1x = 45 + 0 50 + 1x = 45 Add '-50' to each side of the equation. 50 + -50 + 1x = 45 + -50 Combine like terms: 50 + -50 = 0 0 + 1x = 45 + -50 1x = 45 + -50 Combine like terms: 45 + -50 = -5 1x = -5 Divide each side by '1'. x = -5 Simplifying x = -5
| 10(1-2x)=-5(2x-1) | | 9x+9=86-5x | | 8(y+7)=10y+56 | | x+2x+2x-50=3950 | | X-26=180 | | x+138+58+x=180 | | 5*x-x=240 | | 1=1/5(35x+5) | | 1=1/5(35x+15) | | 10x-102=3x-11 | | 8+1.6x=0 | | 13x+48=8x-47 | | 11x-2=10+9x | | 6.3+x=2.7 | | x+9*4=117 | | 2(g-1)=5g-17 | | -6+7x=6(2x-1) | | 7z-5=-50+2z | | x+90=80 | | 4x-(x+1)=1 | | (x+2)-x=2(x+1) | | 13x-1=13x-1 | | 4(x+3)=2(x+6) | | -6*-4+6-3+2=18 | | x^3+20=-4x^2-8x+60 | | -5(4y-3)=4(1-6)+12 | | 6y+1=3 | | 4y-9=-16+3y | | 90-7x=20x+24 | | 13x+2=12x+8 | | x^3+4x^2+8x-40=0 | | 144+10x=284 |